On the occasion of Dushan’s Code - Јанковић, Живорад (Sabornost - The Theological Year-book, 2014)
In the forefront this text deals with the history of transcripts of Dushan’s Code, and there are over twenty of them, which is a rarity among Serbs. The major problem is that of these twenty transcripts — not even two of them are identical, nor any of them contains the complete text of the Code. The popular issues that arise under this headline are actually compilations created on the bases of the contents of all known manuscripts. And when the corpuses were being made, not much seemed to care in what “society” a reputable text was allegedly supposed to be found.